2008
DOI: 10.3181/0803-rm-110
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphisms in Vitamin D Receptor Gene and Susceptibility to Sporadic Prostate Cancer

Abstract: Genetic and environmental factors are involved in prostate cancer (PCa) etiology. Single nucleotide polymorphisms (SNPs) may contribute to the PCa pathogenesis. The goal of this study is to determine the role of vitamin D receptor (VDR) gene polymorphisms and haplotypes in the development and progression of sporadic PCa. One hundred and thirty-three PCa patients and 157 age-matched healthy controls were genotyped for the Apa I (rs7975232), Bsm I (rs1544410) and Taq I (rs731236) polymorphisms in VDR gene by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
(78 reference statements)
2
16
0
Order By: Relevance
“…The distributions of these polymorphisms were in accordance with the Hardy-Weinberg equilibrium among the controls (p = 0.679, p = 0.294, p = 0.204, p = 0.689 and p = 0.230, respectively). The frequencies of selected polymorphisms were similar to those found in previous studies made in the Turkish population [14,22,23,24] as well as to those in other studies in Caucasian populations [13,25,26]. …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The distributions of these polymorphisms were in accordance with the Hardy-Weinberg equilibrium among the controls (p = 0.679, p = 0.294, p = 0.204, p = 0.689 and p = 0.230, respectively). The frequencies of selected polymorphisms were similar to those found in previous studies made in the Turkish population [14,22,23,24] as well as to those in other studies in Caucasian populations [13,25,26]. …”
Section: Resultssupporting
confidence: 76%
“…Among these, Bsm I, Apa I, Taq I, Fok I and Cdx2 are the most studied polymorphisms. It has been reported that these polymorphisms are associated with various diseases including psoriasis, diabetes mellitus and cancers [10,11,12,13,14,15,16]. Up to date, there is only one study showing that the Apa I polymorphism of the VDR gene is associated with vitiligo and might play a role in the etiopathogenesis of the disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30 studies have reported on associations between vitamin D pathway genotypes and risk of prostate cancer (9,13,15,16,21,24,26,27,29,51,53,56,57,62,65,68,70,73,78,83,84,88,89,91,98,99,101,115,128,130) (Supplemental Table 3). A meta-analysis of 14 studies published by Ntais et al (98) in 2003 concluded that four common polymorphisms (BsmI, TaqI, Poly(A) repeat, and FokI) in VDR are unlikely to be major determinants of prostate cancer susceptibility on a population-wide basis.…”
Section: Vitamin D Pathway Genotypes and Prostate Cancermentioning
confidence: 96%
“…50.5% and 14%, respectively. Taq1 gene polymorphism genotypes frequencies differ among different ethnicities, different cancer types (Bid et al, 2005), and methodology by which Taq1 VDR polymorphism was investigated, sample size and vitamin D serum levels (Onen et al, 2008). Among Indian individuals the frequencies of Taq1 variants were 49%, 43% and 8% (Bhanushali et al, 2010) while Japanese study showed 77%, 22% and 1% (Minamitani et al, 1998) and a Turkish, study showed frequency of 40.8%, 47.9% and 11.2% (Dilmec et al, 2009) for TT, Tt and tt respectively.…”
Section: Discussionmentioning
confidence: 99%